Analisis Konsep Kepemimpinan Dalam Organisasi Berdasarkan Ajaran Islam - Asyarah Adinda Syakinah; Ibnu Hanif; Ismail Mubarok (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Organizations need leaders to develop the capabilities of their members. While keadership is the process of achieving organizational goals. Criterialeaders must organize and help their members achieve defined goals.The process of leaders influencing their organization can be done by managing sentences with words, then providing exemplary examples to them by guiding them through advice and guidance. Leaders and leadership must be synchronized because leaders must have the ability to manage and build cooperation with all stake holders and all elements of society. leadership in Islam is a process of governance that does not tolerate tyranny or chaos. Muslim leaders are people who have the principles of life based on the pure principles of Islam, and are fully convinced that in Islam leaders must be trustworthy, fair, deliberative, and tell their members to do good. Islamic leadership is based on Surah Al-Baqarah verse 30, Surah An-Nur verse 55, Surah Shad verse 26 and hadith.In the leadership of Islamic organizations must have leadership criteria, leadership factors, leadership functions and the positive impact of leadership to develop the organization”